The Effect of Multigrade Classes on Cognitive and Non-Cognitive Skills: Causal Evidence Exploiting Minimum Class Size Rules in Italy - Daniele Checchi; Maria De Paola (Institute of Labor Economics (IZA), 2017)
We analyse how schooling in multigrade classes affect the formation of student cognitive and non-cognitive skills. Our identification strategy is based on some institutional features of the Italian educational system establishing a minimum number of students per class. Classes that do not reach the minimum number of pupils are organized in multigrade classes. In addition, the Italian law also establishes a maximum number of students for multigrade classes, leaving a narrow range in the number of students per class which is very similar to small class size in single grade classes when the number of students enrolled in the grade is just above the minimum number of students per class. Using census data on 5th grade Italian students, we find that pupils in multigrade classrooms obtain worse test scores both in literacy and numeracy standardized tests compared to comparable pupils in single grade classroom. While the effect is small and not always statistically significant for the literacy score, we find a large and highly statistically significant effect on the numeracy score. No effect is found on grades assigned by teachers. We also find that pupils placed in multigrade classes tend to have a more external centred locus of control. Our results are robust to different specifications including controls for class size and a number of student and school characteristics.
Keywords: I21; I28; C36; 330; multigrade classes; mixed-age classes; cognitive skills; non-cognitive skills